Structured Data Entry for Reliable Acquisition of Pharmacokinetic Data - Zellner, D.; Schromm, T.; Frankewitsch, T.; Giehl, M.; Keller, F. (Methods of Information in Medicine, 1996)
A pharmacokinetic database was constructed that is as free of errors as possible. Pharmacokinetic parameters were derived from the literature using a text-processing system and a database system. A random data sample from each system was compared with the original literature. The estimated error frequencies using statistical methods differed significantly between the two systems. The estimated error frequency in the text-processing system was 7.2%, that in the database system 2.7%. Compared with the original values in the literature, the estimated probability of error for identical pharmacokinetic parameters recorded in both systems is 2.4% and is not significantly different from the error frequency in the database. Parallel data entry with a text-processing system and a database system is, therefore, not significantly better than structured data entry for reducing the error frequency.
Keywords: Error Frequency; Pharmacokinetic Database; Text Processing; Parallel Data Entry